Urokinase-induced migration of human vascular smooth muscle cells requires coupling of the small GTPases RhoA and Rac1 to the Tyk2/PI3-K signalling pathway - Kiian, Ioulia; Tkachuk, Natalia; Haller, Hermann; Dumler, Inna (Thrombosis and Haemostasis, 2003)
Urokinase-type plasminogen activator (uPA) facilitates cell migration by localizing proteolisys on the cell surface and by inducing intracellular signalling pathways. In human vascular smooth muscle cell (VSMC) uPA stimulates migration via the uPA receptor (uPAR) signalling complex containing the Janus kinase Tyk2 and phosphatidylinositol 3-kinase (PI3-K). We report that active GTP-bound forms of small GTPases RhoA and Rac1, but not Cdc42, are directly associated with Tyk2 and PI3-K in an uPA/uPAR-dependent fashion. Endogenous RhoA, but not Rac1 or Cdc42, was significantly activated in response to uPA. RhoA activation was abolished by cell treatment with two unrelated, structurally distinct, specific inhibitors of PI3-K, wortmannin, and LY294002. Downstream of RhoA, phosphorylation of myosin light chain (MLC) was dramatically upregulated by uPA in a Rho kinase- and PI3-K-dependent manner. Thus, selective Rho kinase inhibitor Y27632 and PI3-K inhibitors wortmannin and LY294002 prevented the uPA-induced stimulation of MLC phosphorylation. Rho kinase inhibition also decreased uPA-stimulated VSMC migration as observed in a Boyden chamber. VSMC immunocytochemical staining demonstrated redistribution of RhoA and Rac1 active forms to the newly formed leading edge of migrating cell. VSMC microinjection with antibodies to either Rho or Rac1 decreased uPA-stimulated cell migration, indicating the involvement of both GTPases in the migration process. Our results provide evidence that the small GTPases RhoA and Rac1, together with Rho kinase, are necessary to mediate the uPA/uPAR-directed migration via the Tyk2/PI3-K signalling complex in human VSMC.
Keywords: Urokinase; urokinase receptor; vascular smooth muscle cells; migration; Rho proteins